2008
DOI: 10.1590/s0004-282x2008000500022
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of cerebrospinal fluid ferritin as a biomarker for CNS malignant infiltration

Abstract: -Several markers have been studied for their ability to make the CNS infiltration diagnosis earlier and more precise; previous studies showed that CSF ferritin concentrations were higher in patients with malignant invasion of CNS. The objective was to determine the importance of CSF ferritin as a biomarker for the diagnosis of CNS neoplasic infiltration. This study is based on 93 CSF samples, divided into five groups: malignant cells present (n13); malignant cells not present (n26); inflammatory neurological d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 21 publications
(40 reference statements)
1
10
0
Order By: Relevance
“…Ferritin is a marker with low specificity, but moderately good sensitivity for neoplastic changes, which can also reach a value above 18 µg/l after bleeding or during infection [35]. In agreement with the literature, we found elevated ferritin in 50% of patients with NM and, of particular note, did not find pathological levels in a control group of 24 patients [33].…”
Section: Reviewsupporting
confidence: 91%
“…Ferritin is a marker with low specificity, but moderately good sensitivity for neoplastic changes, which can also reach a value above 18 µg/l after bleeding or during infection [35]. In agreement with the literature, we found elevated ferritin in 50% of patients with NM and, of particular note, did not find pathological levels in a control group of 24 patients [33].…”
Section: Reviewsupporting
confidence: 91%
“…Besides serum levels, secretory ferritin levels in CSF are also found to increase during malignant infiltration of the central nervous system, and CSF ferritin has been studied for its ability to serve as a biomarker for the diagnosis of brain malignancies . Intriguingly, exhaled ferritin has been reported as potential biomarker for lung cancer …”
Section: Ferritin As a Tumor Markermentioning
confidence: 99%
“…; De Almeida et al . ; Orino & Watanabe ). Serum ferritin levels are positively correlated with body iron reserves in animals, including humans (Walters et al .…”
Section: Introductionmentioning
confidence: 98%
“…Ferritin is present in blood circulation at relatively low concentrations (< 1 mg/mL) (Addison et al 1972;Smith et al 1984a,b;Miyata & Furugouri 1987;Andrews et al 1992bAndrews et al , 1994 and is also found in other extracellular fluids, such as milk and synovial and cerebrospinal fluids Orino et al 2006a;De Almeida et al 2008;Orino & Watanabe 2008). Serum ferritin levels are positively correlated with body iron reserves in animals, including humans (Walters et al 1973;Smith et al 1984a,b;Miyata & Furugouri 1987;Andrews et al 1992bAndrews et al , 1994.…”
Section: Introductionmentioning
confidence: 99%